(untitled) (Acta Polytechnica CTU Proceedings, 2022)
Vacuum glazing products have been in development for the past decades. Such glazing products regularly feature two parallel glass panes that have a small, evacuated gap in their interstitial space. To maintain the vacuum and the form of the glass product, regularly vacuum tight edge seals and a grid of distance pillars are integrated. During the years of development, the major focus was set on the production and durability aspects of the glass products, but relatively few efforts had been conducted towards the integration of such glass products into window constructions. Employing typically used double- and triple glazing windows’ frames does not represent a feasible option. This is due to the specification given by vacuum glazing products, such as their small thickness and the requirement for sufficient glass edge coverage due to the major thermal bridge adjacent to the edge seal. The authors, together with major players from the window producing industry, started a R&D effort that targeted disruptive new concepts for vacuum glass windows. Four different designs were developed that not only integrated vacuum glass products, but also featured unusual opening patterns, the latest generation of electrically driven fitting products, and specific seals. The thermal and acoustical performance of the prototypes was improved during the development via employment of numeric thermal simulation and lab testing. The present contribution illustrates the four prototypes and their performance, which – for instance – pertaining to the UW-value is down to 0.6–0.7 W · m−2 · K−1 at a glass thickness of less than 1 cm.